Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Biaya Modal Ekuitas di Indonesia - Saarce Elsye Hatane; Stefany Lia Jonathan; Maria Brigitta Adriane Irianto (Business Accounting Review, 2021)
The purpose of this study is to investigate the association of Corporate Social Responsibility(CSR) on the Cost of Equity (COE) in Indonesia. This study examines 65 public companies in Indonesiafrom different industries, except the banking and financial sectors, which fully disclose CSR for 5years, from 2015 to 2019. A total of 325 observations are examined using ESG scores as an independentvariable and COE as a dependent variable. As a result, it finds that CSR performance can reduce COE.Companies in Indonesia also need to improve their CSR performance because investors pay attentionto non-financial aspects such as sustainability performance. CSR disclosure is a company's effort to betransparent to stakeholders, thereby reducing information asymmetry. In line with stakeholdertheory, the information provided in support of CSR in the annual report also assists in the needs ofstakeholders. However, this research is limited to Indonesia’s companies only. Different countries mayhave other implications, but countries with similar characteristics as Indonesia may benefit from thisstudy. In addition, the coefficient of determination in this study is 15%. Future research can expandthis research to fill in the remaining 85% of other variables to explain the management of the COE.